2023
DOI: 10.1002/dneu.22918
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of neuropathology in ovine CLN5 and CLN6 neuronal ceroid lipofuscinoses (Batten disease)

Abstract: Sheep with naturally occurring CLN5 and CLN6 forms of neuronal ceroid lipofuscinoses (Batten disease) share the key clinical features of the human disease and represent an ideal model system in which the clinical efficacy of gene therapies is developed and test. However, it was first important to characterize the neuropathological changes that occur with disease progression in affected sheep. This study compared neurodegeneration, neuroinflammation, and lysosomal storage accumulation in CLN5 affected Borderdal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Natural history studies have shown that the cerebellum does not significantly degenerate in CLN5 −/− sheep ( Mitchell et al, 2023 ) and there was also no apparent cerebellar thinning in any treated sheep over the study ( Figure 5 ; Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Natural history studies have shown that the cerebellum does not significantly degenerate in CLN5 −/− sheep ( Mitchell et al, 2023 ) and there was also no apparent cerebellar thinning in any treated sheep over the study ( Figure 5 ; Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 91%
“…By 6 months of age, neuroinflammation in the CLN5 −/− sheep brain is pronounced and spread across the cortical mantle, although the primary visual and parieto-occipital cortices remain the most affected regions ( Mitchell et al, 2023 ). Both GFAP and GSB4 staining of early symptomatic treated brains indicated a halt or slowing of further astrocytosis, brain macrophage formation and recruitment.…”
Section: Resultsmentioning
confidence: 99%
“…Natural history electroretinography studies in untreated CLN5 −/− sheep showed that retinal dysfunction begins around 5 months of age ( Russell et al, 2021 ), and this dysfunction is accompanied by progressive loss of vulnerable neurons in the primary visual cortex and outer nuclear layer and photoreceptor cells in the retina ( Murray and Mitchell, 2022 ; Mitchell et al, 2023b ). IVT administration alone was not sufficient to prevent vision loss in CLN5 −/− sheep, likely due to cortical blindness since the CNS remained untreated ( Murray et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the progressive nature of CLN5 Batten disease, early intervention is predicted to be the most efficacious; however, most human cases are diagnosed when patients are already symptomatic. Therefore, the effect of combined ICV and IVT scAAV9/oCLN5 administration was assessed at three previously identified disease stages–pre-symptomatic (3 months of age), early symptomatic (6 months of age), and advanced symptomatic (9 months of age) ( Mitchell et al, 2023b ). All sheep received the same IVT dose and pre-symptomatic sheep received the previously efficacious ICV dose ( Mitchell et al, 2023a ).…”
Section: Introductionmentioning
confidence: 99%
“…Large animal models for this disease primarily include dogs and sheep [65,66] . Both genetically modified and naturally occurring sheep models are available [61,[65][66][67][68] .…”
Section: Neuronal Ceroid Lipofuscinosis (Batten Disease)mentioning
confidence: 99%